2008
DOI: 10.1021/ja076527u
|View full text |Cite
|
Sign up to set email alerts
|

Rational Design of Macrometallocyclic Trinuclear Complexes with Superior π-Acidity and π-Basicity

Abstract: Density functional theory (DFT) has been used to assess the π-acidity and π-basicity of metalorganic trimetallic macromolecular complexes of the type [M(µ-L)]3, where M ) Cu, Ag, or Au and L ) carbeniate, imidazolate, pyridiniate, pyrazolate, or triazolate. The organic compounds benzene, triazole, imidazole, pyrazole, and pyridine were also modeled, and their substituent effects were compared to those of the coinage metal trimers. Our results, based on molecular electrostatic potential surfaces and positive ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
105
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 111 publications
(108 citation statements)
references
References 48 publications
3
105
0
Order By: Relevance
“…9 [13,14]. The same principle is applicable to these more benign (than Hg analogues) fluorinated coinage metal trimers, because we discovered that they also can complex arenes and sensitize their triplet emissions.…”
Section: External Hae In Trinuclear Silver Binary Adductsmentioning
confidence: 81%
See 1 more Smart Citation
“…9 [13,14]. The same principle is applicable to these more benign (than Hg analogues) fluorinated coinage metal trimers, because we discovered that they also can complex arenes and sensitize their triplet emissions.…”
Section: External Hae In Trinuclear Silver Binary Adductsmentioning
confidence: 81%
“…Because non-fluorinated coinage metal trimers are electron-rich, particularly gold compounds (Figs. 4, 5, 6), [4][5][6][7][8][9][11][12][13][14][15][16][17] such Au 3 species can complex and sensitize the triplet emission of electron-poor organic molecules such as perfluorinated arenes [8,9,11]. The color chromaticity can be easily improved in phosphors synthesized by the strategies in this section because the emission of the binary adducts is essentially the unperturbed T 1 emission of the arene.…”
Section: External Hae In Trinuclear Silver Binary Adductsmentioning
confidence: 96%
“…The simulations revealed that cyclo-[Au(μ-Pz)] 3 trimers act as good π-bases and so should be good models for p-type conductors in molecular electronics. 16 For example, we recently reported the synthesis, characterization and computational modeling of stacked trimers, [Ag(μ-Tz-(n-C 3 F 7 ) 2 )] 3 3 [Au(μ-Pz-(i-C 3 H 7 ) 2 )] 3 (Tz = triazolate), where the cyclo-[Au(μ-Pz)] 3 donor is a p-type conductor in a p-n blended material. 17 In addition, cyclo-[Au(μ-Pz)] 3 complexes have also been used in applications that exploit their catalytic redox activity, metallomesogenic character, and photonic properties.…”
Section: Many Dmentioning
confidence: 99%
“…7,16,29 In addition, we also compared the geometries obtained from B3LYP with the B3PW91 30,31 hybrid functional (results not presented in the article) using the same basis set, which gave similar geometries for coinage metal-trimer complexes. In light of the study of Buhl et al on the geometries of transition metal complexes with different DFT functionals, [32][33][34] we selected the B3LYP functional for the current study.…”
Section: Many Dmentioning
confidence: 99%
See 1 more Smart Citation